THE GOLDEN ORCHARD: A CLOSER LOOK AT THE ECONOMIC BRILLIANCE OF SOPORE’S APPLE INDUSTRY IN KASHMIR - Ishfaq Ahmad Mir; Sarfaraz Ahmad Rather (CV. Radja Publika, 2023)
Abstract The apple is one of the most significant horticultural products and is well-known for its health advantages all over the world. In northern India, Kashmir is one of the main apple-producing regions. The apple business in Kashmir, especially in the region of sopore, is the Valley's main employer and the foundation of its economy. The fame of this fruit extends beyond the borders of the nation and into other countries. It is the sole source of income for many households and employs about 60% of the population overall. During the harvest season, tons of apples are sent to other states in India as well as to countries outside of India, and some are held here in cold storage. Although Kashmir produces several apple varieties, only seven are farmed on a commercial basis. The Mustafa Memorial Fruit Mandi, which is situated near Sopore in the district of Baramulla, is one of the main apple markets in the Valley of Kashmir.